The zen of social media marketing : an easier way to build credibility, generate buzz, and increase revenue - Kabani, Shama Hyder (Dallas, Tex. : Benbella Books ; [Jackson, TN] : Distributed by Perseus Distribution, 2010)
"In 'The Zen of Social Media Marketing', Shama Hyder Kabani, social media expert and president of The Marketing Zen Group (MarketingZen.com), teachesyou the "Zen" of social media marketing: how to use the most popular social media tools to find marketing nirvana" --Cover, p. 4.
Online marketing basics -- Websites, blogs, and SEO -- Social media marketing : what you need to know before you start -- Facebook -- Twitter -- LinkedIn -- Video : the next frontier -- Creating a social media policy for your organization -- A final word on social media : tools for attracting even more business -- Burning questions and answers : taking questions and dishing out answers and advice -- Social media marketing case studies : regular folks, great stories.
Keywords: Internet marketing; Social media; Online social networks